Shaping Character Education: Exploring the 'Dansaa' Program's Management in Early Childhood Educational Institutions - Saepudin, Saepudin; Rozi, Fathor; Qomariyah, Silfiyah Nur; Maghfiroh, Aniq Syahriyatul (JURNAL AL-TANZIM, 2023)
This study aims to analyze the management of strengthening character education through the "Dansaa" program, which an institution has launched for early childhood at one of the early childhood education institutions in Situbondo Regency. This study uses a qualitative case study type approach. Data analysis techniques include data reduction, display, and descriptions or conclusions. Sources of informants were obtained from the school principal, two homeroom teachers, and two accompanying teachers. The research results show that this early childhood education institution first launched a superior program, "Dansaa," in shaping students' character. Secondly, the akhlaqul karimah character management program packaged in the "Dansaa" program was carried out using program planning, implementation of the "Dansaa" program, and follow-up evaluation. The implications obtained in strengthening character education through the "Dansaa" program can instill good morals in early childhood with implemented program activities.